THE INFLUENCE OF ENGLISH USE ON THE CURRENT PROFESSION OF BE/BEC ALUMNI - Asfah, Indrawaty; Mardiani, Reski; Novia, Lely (INDOPEDIA (Jurnal Inovasi Pembelajaran dan Pendidikan), 2024)
This study aims to provide an in-depth insight into the level of English proficiency required for the current BE/BEC alumni profession. The methodology used in this research is descriptive-qualitative, involving eight BE/BEC alumni of Universitas Negeri Makassar. The data was taken through English language tests and interview. The results showed that English proficiency provides a significant competitive advantage in alumni's careers, allows access to wider employment opportunities, and improves communication skills in a global environment. The implications of the findings provide valuable insights for English language learners and professionals to improve their English language skills to support career development and success in an increasingly connected world of work.